(untitled) (International Journal of Physiology, 2019)
Wind instrument is probably the most strenuous activity that requires a high degree of voluntary control over breathing. Pulmonary Function tests help one to understand a person’s respiratory physiology is in either healthy or diseased condition in relation to various environmental conditions. Playing a wind instrument influences the physiological condition of the respiratory tract according to the wind instrument being played and to the musical score so that of which the person’s breathing pattern can be altered. Male Nadhaswaram players between 15–70 years, who had work experience of minimum 3 years and working for minimum 4 hours a day were used as study group and Male Subjects of same age who has the sedentary life style, who are also not any wind instrument players and those who do not have any respiratory illness were taken as control group. Pulmonary function tests of these subjects were done using the “global spirometer” machine. Our work shows that MVV and FEF max is significantly increased in study group and also shows that FVC, FEV1, FEF 25–75% are increased in study group comparatively to the control group. But it progressively decreases as their age(occupational years) advances.